The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/mgg3.1096
|View full text |Cite
|
Sign up to set email alerts
|

A de novo MAPRE2 variant in a patient with congenital symmetric circumferential skin creases type 2

Abstract: Background Congenital symmetric circumferential skin creases (CSCSC) was initially described five decades ago. Exome sequencing has recently revealed the genetic etiology of CSCSC. Pathogenic variants in TUBB (OMIM# 191130) and MAPRE2 (OMIM# 605789) have been linked to CSCSC1 (OMIM# 156610) and CSCSC2 (OMIM# 616734), respectively, in an autosomal dominant manner. Four pathogenic variants in MAPRE2 have been previously reported to be associated with CSCSC2. Methods Whole‐exome sequencing (WES) has been performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Sequencing data were analyzed to identify sequence variants [single nucleotide variant (SNV), insertion/deletion (Ins/Del)] and copy number variants (CNVs) using an in-house pipeline (Fulgent genetics). A phenotype-driven gene list was created to perform a primary variant interpretation for a more targeted analysis ( 4 ). After data analysis, variant filtering, and prioritization, a novel compound heterozygote mutation, c.3596G> A (p.C1199Y)/ex.9del (p.216-248del) in NBAS was identified ( Figure 1A ).…”
Section: Case Presentationmentioning
confidence: 99%
“…Sequencing data were analyzed to identify sequence variants [single nucleotide variant (SNV), insertion/deletion (Ins/Del)] and copy number variants (CNVs) using an in-house pipeline (Fulgent genetics). A phenotype-driven gene list was created to perform a primary variant interpretation for a more targeted analysis ( 4 ). After data analysis, variant filtering, and prioritization, a novel compound heterozygote mutation, c.3596G> A (p.C1199Y)/ex.9del (p.216-248del) in NBAS was identified ( Figure 1A ).…”
Section: Case Presentationmentioning
confidence: 99%
“…Eleven cases of CSC‐KT were confirmed by gene sequencing from 2015 to 2020 (Dentici et al, 2018; Feng et al, 2020; Isrie et al, 2015; Li et al, 2020; Niu et al, 2020) including six cases of the TUBB and five cases of the MAPRE2 variants. Previous studies have shown that two patients with homozygous pathogenic variants in MAPRE2 had severe neurological dysfunction, accompanied by intellectual impairment and seizures, whereas there was no neurological dysfunction in the patients with pathogenic TUBB variants.…”
Section: Discussionmentioning
confidence: 99%
“…16 Interestingly, human mutations in MAPRE2 have been implicated in congenital symmetrical circumferential skin creases type 2, although the genetic and molecular mechanisms are not well defined and the cardiac phenotype has not yet been characterized. 17,18…”
mentioning
confidence: 99%
“…16 Interestingly, human mutations in MAPRE2 have been implicated in congenital symmetrical circumferential skin creases type 2, although the genetic and molecular mechanisms are not well defined and the cardiac phenotype has not yet been characterized. 17,18 To understand the role of EB2 in cardiac arrhythmia, we used the zebrafish model, which exhibits cardiac electrophysiology similar to that of humans. 19 Previously, we knocked out mapre2 acutely in F0 zebrafish using a multi-gRNA CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/clustered regularly interspaced short palindromic repeat-associated protein 9) approach 20 and observed a ventricular phenotype consistent with…”
mentioning
confidence: 99%